Identifying metabolic dysfunction-associated steatotic liver disease in patients with type 2 diabetes mellitus using clinic-based prediction tools - Alkaabi, Juma; Afandi, Bachar; Alhaj, Omar; Kanwal, Darakhshan; Agha, Adnan (Frontiers in Medicine, 2024)
Background: Metabolic dysfunction-associated steatotic liver disease (MASLD), formerly known as nonalcoholic fatty liver disease (NAFLD) is a global cause of chronic liver disease. The prevalence of MASLD is high in patients with type 2 diabetes mellitus (T2DM). Various noninvasive tools like fibrosis-4 index (FIB-4) and NAFLD-fibrosis score (NFS), liver ultrasound, and Fibroscan can aid in the detection of liver fibrosis in MASLD, while the Hamaguchi ultrasound-based liver grading system has demonstrated high sensitivity and specificity comparable to liver biopsy. Objective: We assessed the frequency of MASLD in patients with T2DM using liver ultrasound Hamaguchi score and the accuracy of NFS and Fib-4 in identifying MASLD. Patients and methods: We retrospectively collected data and reviewed the charts of all patients with T2DM who underwent liver ultrasound and laboratory tests, during the past 5 years. Results: A total of 6214 medical records were screened, and only 153 patients (68.6% females; mean age, 59 ± 12.2 years) fulfilled the selection criteria. MASLD was diagnosed using the Hamaguchi grading criteria in 45.1% of patients. A high/intermediate NFS had higher sensitivity (79.7%) for diagnosing MASLD, with specificity of 10.7%, while high/intermediate Fib-4 score showed only 30.4% sensitivity but higher specificity of 54.8%. Conclusion: Our study indicates that MASLD is frequent in patients with T2DM and clinical prediction tools like NFS and Fib-4 can be applied in clinic/primary care setting with variable results.